Consumers' willingness to pay for pork produced with different levels of antibiotics. Issue 1 (29th January 2022) - Paudel, Bindu; Kolady, Deepthi; Grebitus, Carola; Roy, Aniruddha; Ishaq, Mariam
Abstract: Compared with the EU, regulations on antibiotic use in livestock are less stringent in the USA. If consumers prefer non-antibiotic or minimal antibiotic-use meat, labeling different levels of antibiotic use in the USA could have the potential to mitigate the development of antibiotic-resistant livestock. This study used a survey of 660 US consumers to estimate willingness to pay (WTP) for pork chops from pigs raised with different levels of antibiotic use. Results show that WTP for antibiotic-free pork chops is higher compared with WTP for pork chops produced with minimal use of antibiotics for disease treatment and conventional use of antibiotics for growth promotion. These findings suggest that it could be beneficial to differentiate usage levels of antibiotics when labeling pork products rather than stating 'use' or 'no use'.